2020
DOI: 10.21037/jtd.2020.01.54
|View full text |Cite
|
Sign up to set email alerts
|

Safety of early orthopedic surgery in patients with intermediate/low- or low-risk pulmonary embolism

Abstract: Background: Preoperative pulmonary embolism (PE) is one of the comorbidities in patients with hip fracture. However, previous studies have not identified the optimal timing of surgery in these patients, who might require early surgery. This study aimed to investigate the safety and clinical feasibility of early surgery in patients with hip fracture and acute PE. Methods: The medical records of 156 patients with hip fracture, who were suspected to have PE and underwent pulmonary computed tomography angiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In a retrospective cohort study, Kim et al, found no significant difference in major or non-major bleeding, transfusion rates or length of stay at 3-month follow-up in hip fracture patients diagnosed with PE pre-operatively relative to a non-PE patient cohort with suspected VTE 2169 . Of note, 95.6% of the PE cohort received therapeutic anticoagulation postprocedure 2169 , hence suggesting that peri-operative empirical treatment of VTE may be safe even if early surgery is advocated. However, peri-operative major and non-major bleeding rates remained significant, which were 21.1% and 13.3%, respectively, at 3-month follow-up in the PE cohort 2169 Indeed, the proportion of non-PE patients administered therapeutic anticoagulation for suspected VTE pre-operatively was not reported and may have confounded the comparison in this study.…”
Section: Jean-yves Jennymentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective cohort study, Kim et al, found no significant difference in major or non-major bleeding, transfusion rates or length of stay at 3-month follow-up in hip fracture patients diagnosed with PE pre-operatively relative to a non-PE patient cohort with suspected VTE 2169 . Of note, 95.6% of the PE cohort received therapeutic anticoagulation postprocedure 2169 , hence suggesting that peri-operative empirical treatment of VTE may be safe even if early surgery is advocated. However, peri-operative major and non-major bleeding rates remained significant, which were 21.1% and 13.3%, respectively, at 3-month follow-up in the PE cohort 2169 Indeed, the proportion of non-PE patients administered therapeutic anticoagulation for suspected VTE pre-operatively was not reported and may have confounded the comparison in this study.…”
Section: Jean-yves Jennymentioning
confidence: 99%
“…In a retrospective cohort study, Kim et al, found no significant difference in major or non-major bleeding, transfusion rates or length of stay at 3-month follow-up in hip fracture patients diagnosed with PE pre-operatively relative to a non-PE patient cohort with suspected VTE 2169 . Of note, 95.6% of the PE cohort received therapeutic anticoagulation post-procedure 2169 , hence suggesting that peri-operative empirical treatment of VTE may be safe even if early surgery is advocated.…”
Section: - Is There a Role For Empirical Treatment Of Patients With S...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is precedence for early surgical intervention in patients with low-intermediate risk pulmonary embolism. A retrospective cohort study of 140 patients who underwent orthopedic surgery found no difference in major bleeding episodes between the PE and non-PE groups when operated on within 30 days of diagnosis (21.1% vs 16%; p=0.463) [ 5 ]. Furthermore, there was no significant difference in bleeding risk or duration of hospitalization when controlling for patients with an inferior vena cava filter placement.…”
Section: Discussionmentioning
confidence: 99%